Psychological Flexibility and Self-Compassion in Gay and Heterosexual Men: How They Relate to Childhood Memories, Shame, and Depressive Symptoms. Issue Volume 11:Issues 2(2017) (3rd April 2017) - Matos, Marcela; Carvalho, Sérgio A.; Cunha, Marina; Galhardo, Ana; Sepodes, Carlos
ABSTRACT: This study explores differences between men who are gay ( n = 53 ) and men who are heterosexual ( n = 52 ) regarding memories of shame events and of warmth and safeness experiences with parents during childhood and adolescence, self-compassion, psychological flexibility, internal shame, and depression. Also, it aims to explore whether psychological flexibility and self-compassion play a role in the association between these memories and internal shame and depressive symptoms. Results confirmed the mediating role of psychological flexibility and self-compassion. These findings suggest the appropriateness of promoting acceptance and self-compassion towards difficult memories in a therapeutic setting with men who are gay experiencing shame and depressive symptoms.